Penerapan Teknologi Tepat Guna Rocket Stove Incinerator dalam Pengelolaan Sampah Rumah Tangga melalui Pendekatan Participatory Action Research - Muhammad Muryanto; Trio Nur wibowo; Syaukaty Yasinta; Irfauji Firman Hidayat (LPPM Universitas Harapan Bangsa Purwokerto, 2025)
Limited facilities and infrastructure for waste management are among the main factors contributing to the low level of environmental awareness in Gumiwang Village, Purbalingga Regency. This science and technology–based community service program aims to formulate an innovative strategy to address environmental issues faced by the local community. The strategy is implemented through the design and development of an appropriate technology in the form of a rocket stove incinerator. The community service model adopts a Participatory Action Research (PAR) approach, which emphasizes collaborative problem-solving through a shared learning process between students and community members. The PAR approach enables the community to actively participate in all stages of the program, from problem identification to solution implementation. The results of the program indicate an improvement in community understanding of the importance of sustainable waste management. The application of the rocket stove incinerator as a simple technology has successfully reduced uncontrolled waste disposal practices, particularly the disposal of waste into water bodies. Furthermore, participatory community involvement has strengthened a sense of collective responsibility in maintaining environmental cleanliness. Changes in community mindset and behavior serve as key indicators of the program’s success in supporting sustainable waste management at the village level